OC-049 Rectal Neuroendocrine Tumours: Management And Survival In 60 Patients. (9th June 2014) - Naik, K; Rossi, R; Caplin, M; Toumpanakis, C
Abstract : Introduction: Rectal neuroendocrine tumours (rNETs) are increasing in incidence, with more found incidentally on routine colonoscopy. Our aim is to retrospectively analyse a cohort of rNETs to characterise diagnostic features and clinical behaviour. Methods: Patients (pts) with confirmed diagnosis of rNET were identified from a database. Results: 60 pts evaluated, median age 55 years (range 23–78). Most common presentation was rectal bleeding n = 29 (48%). 29/60 pts had tumour <1 cm, 7/60 pts 1–2 cm, 22/60 >2 cm, 2/60 size was unknown. Of patients with tumour size <1 cm, 3/29 did not require endoscopic follow-up (pT1a) and of the other 26, none had evidence of recurrence on endoscopic follow-up (follow-up range 6 to 88 m). 24/60 pts had metastases at presentation, 5/60 developed metastases during follow-up (of these 29 pts 86% liver, 40% bone, 10% lung). Of 29 pts with metastases, 24/29 had somatostatin receptor imaging with 62% avid uptake. Chromogranin A available in 23/29 pts: not elevated in 83%. Of 29 pts with metastases, 19/29 had chemotherapy, 10/29 somatostatin analogues (SST), 15/29 surgery and 10/29 peptide-receptor-radionuclide-therapy (PRRT). Chemotherapy: 1/19 pts partial response, 2/19 stable disease (SD), 12/19 progressive disease (PD) (median time to progression 4 months (m)); 4/19 no data. PRRT: 4/10 had SD (follow-up range 24 to 53 m), 4/10 PD (median time to progression 4 m, range 2–9), 2/10 no data. SST: 2 sustained SD (range 12–27 m), 7/10 PD, (median time to progression 3m, range 2–5); 1/10 no data. During median follow-up of 20 m (range 3–170 m), 100% of pts with primary tumour <1 cm, 86% with tumour size 1–2 cm, and 25% with size >2 cm are currently alive. Tumour size >2 cm have poorer outcome than the other 2 groups (p < 0.001). Conclusion: Tumours >2 cm are associated with poor prognosis. Chromogranin A is mostly normal even in advanced disease. Prospective studies are needed to determine progression free survival data for systemic therapy. Disclosure of Interest: None Declared.